Subjective well‐being among rheumatoid arthritis patients. (9th October 2019) - Kageyama, Goichi; Onishi, Akira; Ueda, Yo; Naka, Ikuko; Tsuda, Kosaku; Okano, Takaichi; Akashi, Kengo; Nishimura, Keisuke; Sendo, Sho; Saegusa, Jun; Morinobu, Akio
Abstract: Aim: Subjective well‐being (SWB) is a psychological construct that is synonymous with happiness. Many variables including age, sex, income, employment, and marital status are related to SWB. Health is also an important determinant of SWB that can be adversely affected in patients with chronic conditions such as rheumatoid arthritis (RA). In this study, we evaluate the SWB of RA patients and compare it with that of healthy controls. Methods: We obtained the original dataset from the "Quality of Life Survey, 2013", which was conducted by the Economic and Social Research Institute, Cabinet Office, Government of Japan. In this survey, SWB was determined by asking participants to rate their happiness between 0 (very unhappy) and 10 (very happy). The survey also included a 56‐point questionnaire regarding well‐being‐related variables. This questionnaire was administered to RA patients recruited from Kobe University Hospital, and clinical and treatment data were simultaneously collected. Results: Multivariate analysis revealed that RA patients with high or moderate disease activity had SWB scores that were similar to those of controls. However, the SWB scores of RA patients in remission or with low disease activity were higher than those of controls ( P  = .013). SWB was associated with household income, self‐assessment of living costs, self‐assessment of health, depression/ anxiety, and social connection. Conclusions: For RA patients, achieving the therapeutic target can result in better SWB than that of healthy controls. Financial status, self‐assessment of health, psychological stress, and social network are also important determinants for the SWB of RA patients.